HUMAN INTERLEUKIN-1 RECEPTOR ASSOCIATED KINASE-2 (IRAK-2) IS ESSENTIAL FOR TOLL-LIKE RECEPTOR-MEDIATED TRANSCRIPTIONAL AND POSTTRANSCRIPTIONAL REGULATION OF TNFα - BOWIE, ANDREW (My University, 2011)
Toll-like receptors (TLRs) are pattern recognition receptors that recognise microbial ligands and subsequently trigger intracellular signalling pathways involving transcription factors such as NF?B and MAPKs such as p38. TLR signalling can regulate both transcriptional and post-transcriptional events leading to altered gene expression, and thus appropriate immune responses. The interleukin-1 receptor associated kinase (IRAK) family comprises four kinases that regulate TLR signalling. However, the role of IRAK-2 has remained unclear, especially in human cells. Recent studies using cells from in-bred IRAK-2-/- mice showed that murine IRAK-2 was not required for early TLR signalling events, but had a role in delayed NF?B activation and in cytokine production. IRAK-2 in mice has four splice variants, two of which are inhibitory, while human IRAK-2 has no splice variants. Thus IRAK-2 in mice and humans may function differently, and therefore we analyzed of the role of IRAK-2 in TLR responses in primary human cells. SiRNA knockdown of IRAK-2 expression in human peripheral blood mononuclear cells showed a role for human IRAK-2 in both TLR4 and TLR8-mediated early NF?B and p38 MAP kinase activation, and in induction of TNF mRNA. These data conflict with findings from the in-bred IRAK2-/- mice, but concur with what has been seen in wildderived mice for TLR2. Moreover, human IRAK-2 was required for regulating MyD88- dependent TNF? mRNA stability via the TNF 3?UTR. Collectively these data demonstrate for the first time an essential role for IRAK-2 in primary human cells for both transcriptional and post-transcriptional TLR responses.
PUBLISHED
PubMed ID: 21606490
Keywords: Toll-like receptors (TLRs); Immunology, Inflammation & Infection